Análise de dispositivos legais para o ensino de surdos: alguns apontamentos - Nunes, Francisco Lucas Dias (Universidade Federal Rural do Semi-Árido, 2019)
This dissertation presents as a discussion axis a analyzeon legal provisions that support the rights of deaf people to education and formal teaching processes. The Federal Constitution of 1988 points to the guarantee of the educational rights of the deaf -as well as other persons with disabilities -which, unfortunately, was not enough to meet the specific needs of the deaf community, whichhas been gaining more and moresocial space. Faced with this problem, we ask: what is legally assured for deaf education in Brazil? In order to elaborate reflexive considerations, we propose to analyze the Law 13.146 / 2015 of the person with disabilities -LPI, the Libras Law 10.436 / 2002 and the Decree 5.626 of December 22, 2005, with the purpose of capturing what these provisions advocate and reflect with them the deaf education from the legal point of view. This is a qualitative research, in which we use the documentary analysis, based on guidance from Lüdke and André (1986), Moreira (2002) and Lakatos (1991). From the analysis of the legal provisions we could identify advances concerning the social presence of the deaf community, legitimized by the recognition of the term deafness and the cultural identity of the deaf, as well as Libras as the second official language of Brazil. We realize that Libras arises in the legal provisions, initially in a timid way, which is expanding expressed by Decree 5,626 of December 22, 2005. The research also led us to know the guidelines for the training of Libras teacher and Libras instructor, proposing that the training of professional interpreters take place in institutions of higher translation and interpreting courses with qualification in Libras / Portuguese language, enabling this professional to work in thekindergarten,elementary schooland higher education.
Keywords: Libras; Inclusão; Educação; Dispositivos legais; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS